Respuesta :
nvm i found the answer
Let's solve your equation step-by-step.
2(2x+1)=3(x+2)
Step 1: Simplify both sides of the equation.
2(2x+1)=3(x+2)
(2)(2x)+(2)(1)=(3)(x)+(3)(2)(Distribute)
4x+2=3x+6
Step 2: Subtract 3x from both sides.
4x+2−3x=3x+6−3x
x+2=6
Step 3: Subtract 2 from both sides.
x+2−2=6−2
x=4
Answer: 4
Step-by-step explanation:Let's solve your equation step-by-step.
2(2x+1)=3(x+2)
Step 1: Simplify both sides of the equation.
2(2x+1)=3(x+2)
(2)(2x)+(2)(1)=(3)(x)+(3)(2)(Distribute)
4x+2=3x+6
Step 2: Subtract 3x from both sides.
4x+2−3x=3x+6−3x
x+2=6
Step 3: Subtract 2 from both sides.
x+2−2=6−2
x=4
Read more on Brainly.com - https://brainly.com/question/16534301#readmore